The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/biom8010002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Simultaneous Production of Xylitol and Ethanol from Sisal Fiber

Abstract: Recent years have seen an increase in the use of lignocellulosic materials in the development of bioproducts. Because sisal fiber is a low cost raw material and is readily available, this work aimed to evaluate its hemicellulose fraction for the simultaneous production of xylitol and ethanol. The sisal fiber presented a higher hemicellulose content than other frequently-employed biomasses, such as sugarcane bagasse. A pretreatment with dilute acid and low temperatures was conducted in order to obtain the hemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Dilute sulfuric acid is the most commonly used acid for the pretreatment of various biomass feedstocks. Among acidic solutions, H2SO4 is the preferred option for acidic pretreatment (Santos et al 2018;Shimizu et al 2018;Xavier et al 2018). Despite the efficiency of diluted acid, there remains a concern about the formation of inhibitors (Jędrzejczyk et al 2019), such as hydroxymethylofurfural (HMF), furfural, and acetic acid.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Dilute sulfuric acid is the most commonly used acid for the pretreatment of various biomass feedstocks. Among acidic solutions, H2SO4 is the preferred option for acidic pretreatment (Santos et al 2018;Shimizu et al 2018;Xavier et al 2018). Despite the efficiency of diluted acid, there remains a concern about the formation of inhibitors (Jędrzejczyk et al 2019), such as hydroxymethylofurfural (HMF), furfural, and acetic acid.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Earlier it was thought that after pretreatment, LCR has to be detoxified before fermentation but some of the recent work suggested that pretreated hydrolysate can be used without detoxification. Among different LCRs, sisal fibers having higher availability as low cost raw material have been evaluated for simultaneous production of xylitol and [32]. Rapeseed straw hemicellulosic hydrolysate was also evaluated for xylitol production by Debaryomyces hansenii and Candida guilliermondii, using different hydrolysate detoxification strategies.…”
Section: Ovat Analysis For Xr Productionmentioning
confidence: 99%
“…This study addresses these concerns by exploring the integration of innovative materials, namely Hypo sludge and novel sisal fiber, into M25 grade concrete. The novelty lies in the synergistic effect of these materials on mechanical strength and durability, offering an ecofriendly and sustainable alternative to conventional concrete (Damião(Damião Xavier et al 2018).…”
Section: Introductionmentioning
confidence: 99%